Best Practices for Retaining Public Speaking Students - Kimberly M. Weismann; Shannon B. Vanhorn; Christina G. Paxman (Central States Communication Association, 2018)
This article draws on existing communication research and praxes to share the best practices for retaining students enrolled in the introductory public speaking course. Among the many important pedagogical practices that communication scholars have documented, this article highlights the value of 10 best practices: instructor use of immediacy and confirmation; instructor inclusion of written prescriptive feedback, peer feedback workshops, low-stakes assignments, applied assignments, and individual speech preparation tools; and instructor participation in out-of-class communication, online office hours, and classroom-connectedness.